Halal Tourism Village Development Concept - Fardani, Irland; Damayanti, Verry; Syaodih, Ernady; Burhanudin, Hani; Widagdo, Rama Arianto (MIMBAR : Jurnal Sosial dan Pembangunan, 2025)
Kutawaringin Village is the first village to officially become the first economy-based village in Bandung Regency. Kutawiringin village has good potential to be developed, Tourism activities in Kutawaringin village are centered on Cipeer Hill. In the Kutawaringin village there is a problem with the planning of the tourism and there is nothing unique in the tourism. In this study a participatory approach was used or in tourism it is better known as Community Based Tourism Development. The analysis used in this study is the 4A analysis. From the results of the analysis carried out, it was found that the village of Kutawarining wants to add more attraction in their tourism area, mantain the local culture and promote the traditional foods form their local community. All of these additional components are covered by the concept of halal tourism, so tourism in Kutawaringin has unique theme of toursim if it compare with another tourism area.